Pendampingan Pembuatan Mural Sebagai Upaya Meningkatkan Edukasi Belajar Serta Perbaikan Visual Sekolah - Zhilli Izzadati khairuni; Rumilla Harahap; Kemala Jeumpa (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
The target of this community service activity is a school located on the outskirts of the city of Medan, precisely Perumnas Simalingkar Medan Tuntungan. This school is a school that has a vision and mission of helping the surrounding community to go to school at low cost and even free for certain family conditions. Apart from these conditions, currently there are new private schools with low tuition fees and better physical appearance so that some parents choose to move their children on the grounds that good school facilities will support good development for students. With these conditions, the school operational costs for building maintenance are slowly being allocated no longer. This is what makes the PKM team plan to provide insights related to physical buildings in accordance with their field of science. One of the efforts that can be made to create good and attractive visuals is to improve the physical building. This effort is in the form of mural art applications, apart from being considered as beautifying the physical appearance of the building, this mural art can also strengthen the character of an area. The method used is the socialization method, making design concepts, then practicing with the guidance of making murals, as well as monitoring and evaluation. In this activity, the stages taken are providing preliminary material in the form of architectural understanding, the preparation stage for making a mural design and the painting stage. The resulting mural is in the form of an educational mural with several kinds of knowledge. The results of this activity are expected to increase the economy, increase the science of arts for selected partners as well as improve the visuals of school buildings.